Psycholinguistic Study of Language Disorders in Autistic Children - Indriyani, Mey Linda (Bulletin of Science Education, 2021)
Barriers experienced by someone in language is a language disorder, language disorders is a study of discussion in psycholinguistics. The purpose of this journal is to provide data relating to the relationship between psycholinguistics and disability in language in autistic children. The method is in the form of library research by collecting data from various scientific references. Based on data from several scientific references that are collected, analyzed, and studied, and get results that children with autism are influenced by the ability to interact and communicate because there is a behavior disorder caused by nerve development. Interference in speech is the main symptom caused by children with autism. Disability and deficiencies in communicating using verbal or other needs for children with autism will experience obstacles to get and understand communication in the community. language disorders is a study of discussion in psycholinguistics. In psycholinguistics a person applies an archetype in language acquisition. In the process of language acquisition, one's ability to speak can be influenced by mental or psychological symptoms. Mental or psychological symptoms, including those experienced by children with autism. Keywords: Psycholinguistics, Language Disorders, Autistic Children